Pembuatan Instrumen Teknologi Perencanaan Menu Diet - Putri, Pratiwi Hariyani; Putri, Fildzah Karunia; Sulistiyani, Endang (citeus, 2020)
This study aims to create a Diet Menu Planning Technology Instrument. The model used for making the instrument is procedural. This model is a descriptive model with a description of the development steps according to the research needs. R and D was chosen as the procedural approach. The development steps are (1) analysis of the weaknesses of the diet menu-planning instrument currently in use, (2) analysis of the instrument specifications for new technology, (3) instrument design, and (4) instrument testing. The resource persons in this study were lecturers of the nutrition study program and selected using purposive sampling technique to obtain data on the needs for dietary menu planning technology instruments. The types of data produced in this study are qualitative and quantitative data. The final product of this diet menu planning automatic instrument is named